Ponseti method for treatment of idiopathic congenital talipes equinovarus at tertiary care center in India - Lingayat, Maruti B.; Dhamale, Sourabh S.; Mate, Gaurav B. (International Journal of Research in Orthopaedics, 2021)
Background: Different treatment methods were tried with variable success rates but Ponseti method of serial casting and manipulation stood apart due to better understanding of foot biomechanics and became accepted choice of treatment worldwide. Methods: 50 patients were enrolled in the study out of which 40 were available for final follow-up. We studied 40 cases during October 2018 to December 2020 at Government Medical College, Aurangabad. Out of 40 cases 31 were male and 9 were female. 25 were unilateral and 15 were bilateral. All cases were idiopathic. 4 inches Plaster of Paris (POP) bandages were cut into half and such 2 inches POP bandages were used for casting. Tenotomies were performed under controlled environment of Operation Theater with general anaesthesia. Number 12 surgical blade was used. Dennis-Browne splint was used for maintenance of correction. Results: Out of total 55 feet studied, 10 feet (18.18%) required tendo Achilles tenotomy and 45 feet (81.82%) were treated with casting alone. There were 8 cases of relapses (20%). All relapsed cases were treated with repeat casting as per Ponseti protocol and none of them required repeat tenotomy. Complications related to plaster were minimal and there were no incidence of rocker bottom deformity. Conclusions: We conclude that in a low income developing country like India where case load is very high; Ponseti method is effective, inexpensive form of treatment with minimal complications. Need for extensive soft tissue procedures vastly reduced with this method.